THE INFLUENCE OF GUIDED DISCOVERY LEARNING MODEL WITH GUIDED INQUIRY BASED LEARNING MODULE BASED CONCERNING TO NATURALISTIC INTELLIGENCE VII GRADE STUDENT AT SMP MUHAMMADIYAH 8 SURAKARTA IN ACADEMIC YEAR 2014/2015 - Meti Indrowati, Muh Syarif Hidayatullah,Meti Indrowati (P Biologi FKIP UNS Surakarta, 2015)
The aims the research determine the effect of the application guided discovery learning model with guided inquiry-based learning module concercing to naturalistic intelligence student grade VII at SMP Muhammadiyah 8 Surakarta in academic year 2014/2015. This study included in the quasi-experimental research. The study design was a Post-Test Only Nonequivalent Group using experimental class (guided discovery learning with the learning modules) and the control class (guided discovery learning). The population of this research was all students VII grade of SMP Muhammadiyah 8 Surakarta in academic year 2014/2015. The sampling technique using cluster sampling method and taken two classes, one class as the experiment and the class as a control. Data collection techniques using test descriptions, observation sheets, and school documents. Hypothesis testing using t-test. The results showed that the students' intelligence naturalistic experimental group and the control group was significantly different. The experimental group value of average general naturalistic intelligence 53.087 with a value 2,63 of classifying aspects and 1.35 of know. Control group with a value of naturalistic intelligence 45,810 with classifying aspects 2,30 and know aspect 1,29. Based on the research proficiency level can be concluded that the application of guided discovery learning model with guided inquiry learning modules affect to the naturalistic intelligence at seventh grade students of SMP Muhammadiyah 8 Surakarta in academic year 2014/2015. Keywords: guided discovery learning, learning module, naturalistic intelligence